Use of Photovoltaic Panels with Synchronous Generator - Aladag, Canan; Orhan, Ahmet (Ieee, 2016)
Due to rapid consumption of energy source in nature, and the self-non-renewal sources such as patrol, coal etc. that causes damaging to environment, using renewable energy source is getting inevitable position. Solar energy is used in many areas together with energy systems. In such systems, the main purpose is that the ratio of cost/efficiency is to keep as low as possible. In this study, a power generation plant based on photovoltaic energy is modeled. In photovoltaic systems, providing energy even in transient regime and power continuity for unexpected situations is very important. The aim of this study is that supplying DC motor with voltage by obtaining from photovoltaic panel as well as providing the continuity of system with driving synchronous generator by DC motor. The reliability of the obtaining results is proven under different load profiles in designed system.
Fotovoltaik panellerin senkron jeneratör ile kullanimi
National Conference on Electrical, Electronics and Biomedical Engineering (ELECO) -- DEC 01-03, 2016 -- Bursa, TURKEY